The 2011 break in the part-time indicator and the evolution of wage inequality in Germany - Bernd Fitzenberger; Arnim Seidlitz (Journal for Labour Market Research, 2020)
German social security records involve an indicator for part-time or full-time work. In 2011, the reporting procedure was changed suggesting that a fraction of worker recorded to be working full-time before the change were in fact part-time workers. This study develops a correction based on estimating the probability of being a part-time worker before and after the break. Using the correction, the paper confirms that the rise in wage inequality among full-time workers in West Germany until 2010 is not a spurious consequence of the misreporting of working time.
Keywords: C80; J31; J60; 330; Germany; Part-time indicator; SIAB7514; Wage inequality